(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
This article develops the theoretical basis of the study of the marketing environment of the enterprise, in particular, the interaction of business, consumers (users, customers) and the state with the help of marketing tools. The need to find common rational solutions of the main economic actors – business, consumers and the state – to increase the pace of innovative transformations that meet national interests and aimed at economic development at all levels of government through the widespread use of marketing tools. Emphasis was placed on the urgent need for business cooperation with all economic actors in view of the rapid development of digital technologies, pandemic sentiment in society and the need for cohesion. It is shown that the purpose of cooperation is mutually beneficial cooperation and the formation of a strong ecosystem of the country. The peculiarities and the main tasks of innovative marketing at the enterprise are singled out and analyzed. The parameters of evaluating the effectiveness of entrepreneurial activity of the marketing sector with the help of financial and non-financial indicators of BSC are determined.